Fast synthesis of large-scale single-crystal graphene with well-defined edges upon sodium chloride addition. (March 2020) - Kim, Su Han; Jiang, Jie; Jang, Suhee; Lee, Jae Hyung; Yang, Dong Won; Chang, Won Jun; Shin, Jae Hyeok; Oh, Nuri; Kim, Jaeyong; Pachter, Ruth; Park, Won Il
Abstract: There have been many efforts to grow high-quality, single-crystalline graphene on a cheap substrate, such as a metal foil. However, control of nucleation and growth of individual flakes, as well as their seamless stitching, remains elusive. Here we demonstrate a new strategy to fast and facile synthesis of large scale single-crystal graphene on copper foil. Polycrystalline Cu foils were first converted to single-crystal Cu foils through high-temperature annealing processes. Then, a sodium chloride (NaCl) additive was introduced during chemical vapor deposition growth of graphene on the Cu foils. Investigation of early stage growth in this process suggests that the NaCl additive enhances nucleation events and depresses dendritic growth, producing high-density graphene flakes (GFs) with crystallographically well-defined edges: (i) rectangular-shaped GFs on Cu(100) and (ii) hexagonal-shaped GFs on Cu(111). Density functional theory calculations show that NaCl can assist in the elimination of remnant oxygen atoms on the Cu surface and promote epitaxial interactions between Cu and graphene. This behavior was further exploited to achieve large-scale single-crystal graphene through epitaxial, seamless stitching of hexagonal GFs within 90 s. Graphical abstract: Image 1